Online Parsing of Sports Coaching Video Through Intrinsic Motion Analysis - KOKARAM, ANIL CHRISTOPHER; RING, DANIEL (My University, 2007)
Automatic record and review of actions in sports training sessions is of great benefit to both coach and athlete. Many coaching sessions involve repetition of particular actions to hone technique, such as a swing from a tennis racket, golf club, or cricket bat. These actions can be defined by unique motion signatures. A method is proposed to parse the training video using motion into browse-able actions. The method aims to avoid the intensive explicit computation of player silhouette and motion vector fields, allowing for a real-time, online application on standard hardware.
PUBLISHED
Keywords: Intrinsic; Motion; Estimation; Contentbased; Analysis; Sports; Coaching